2022
DOI: 10.1017/s0007114522000289
|View full text |Cite|
|
Sign up to set email alerts
|

Can individual fatty acids be used as functional biomarkers of dairy fat consumption in relation to cardiometabolic health? A narrative review

Abstract: In epidemiological studies, dairy food consumption has been associated with minimal effect or decreased risk of some cardiometabolic diseases (CMD). However, current methods of dietary assessment do not provide objective and accurate measures of food intakes. Thus, the identification of valid and reliable biomarkers of dairy intake is an important challenge to best determine the relationship between dairy consumption and health status. This review investigated potential biomarkers of dairy fat consumption, suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…The plasma PL-FA profile associated with the high-SFA diet was characterised by higher proportions of pentadecanoic acid (C15:0) and vaccenic acid (C18:1 n −7 trans ). These two FAs have been previously used as biomarkers of dairy fat consumption, as odd-chain SFAs and ruminant TFAs are synthesised in the rumen of cows before being integrated into the fat fraction of dairy foods [ 19 , 38 ]. As plasma PL-FAs are thought to reflect short to medium-term dietary FA consumption [ 12 , 16 , 17 ], the importance of these two FAs in the high-SFA diet plasma PL-FA profile may be explained by a higher consumption of full-fat dairy products, which contributed to 39.6% of dietary total fat and 50.1% of dietary SFAs during the high-SFA diet.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The plasma PL-FA profile associated with the high-SFA diet was characterised by higher proportions of pentadecanoic acid (C15:0) and vaccenic acid (C18:1 n −7 trans ). These two FAs have been previously used as biomarkers of dairy fat consumption, as odd-chain SFAs and ruminant TFAs are synthesised in the rumen of cows before being integrated into the fat fraction of dairy foods [ 19 , 38 ]. As plasma PL-FAs are thought to reflect short to medium-term dietary FA consumption [ 12 , 16 , 17 ], the importance of these two FAs in the high-SFA diet plasma PL-FA profile may be explained by a higher consumption of full-fat dairy products, which contributed to 39.6% of dietary total fat and 50.1% of dietary SFAs during the high-SFA diet.…”
Section: Discussionmentioning
confidence: 99%
“…These findings from plasma PL-FAs are consistent with those from previous RCTs, which reported moderate but consistent associations between total dairy consumption and circulating levels of pentadecanoic acid in serum or plasma total lipids [ 50 52 ]. However, these findings from the RISSCI-1 study provide novel evidence for the utility of vaccenic acid as a biomarker for dairy fat consumption, a ruminant TFA that has been previously under studied in intervention studies [ 19 ]. The predictive accuracy of circulating pentadecanoic or vaccenic acids as biomarkers of dairy fat consumption, reflected by the predictive R 2 value, was significantly improved when using prospective multiple regression models (i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Herein, odd-chain saturated fatty acids are the most commonly used biomarkers of dairy intake. 10 Not only odd-chain saturated fatty acids are suspected to have beneficial effects on cardiometabolic health but they have been repeatedly associated with lower risk of cardiometabolic diseases. 11 However, their use remains criticized since they lack of specificity with regard to dairy consumption.…”
Section: See Related Article Pp 1617-1628mentioning
confidence: 99%
“…11 However, their use remains criticized since they lack of specificity with regard to dairy consumption. 10,11 Besides, from a clinical standpoint, randomized controlled feeding trials on the impact of dairy consumption on traditional cardiometabolic risk factors (eg, blood pressure, blood lipids, subclinical inflammation, insulin resistance, vascular function) have also been highly inconclusive. 12 While meta-analyses of randomized controlled feeding trials found no evidence of potential harmful effects of dairy consumption on traditional cardiometabolic risk factors, no evidence of potential benefits resulting from the consumption of these foods was also reported.…”
Section: See Related Article Pp 1617-1628mentioning
confidence: 99%